(untitled) (Nordic Journal of African Studies, 1999)
The desire for a renaissance in present-day Africa must be evaluated against the background of forty years of post-independence economic delusion and political chaos. The continent’s mediocre economic performance and its continued and increasing marginalization in the international economic order is likely to be intensified and consummated by the present trend towards globalization unless viable and novel alternatives are pursued. The central concern of this article is two-fold. We explain the causes of the failure of earlier attempts at African renaissance such as foreign development aid, Structural Adjustment Program, and Continental Union Government. We then proceed to suggest viable alternatives. Our major thesis is that these attempts failed principally because existing political and economic structures are not integrated enough and hence patently incapable of meeting the challenges of economic emancipation envisaged by African renaissance. Fundamental to this is the fact the considerations of sovereignty have often stifled private and local initiative at economic integration. We further assert that even if foreign development aid was gratuitous and an inevitable panacea for Africa’s economic doldrums, African states would still need to integrate their economies and to surrender of a measure of their sovereignty in order for foreign aid to succeed. We posit that the fundamental solution to the problems of Africa’s economic backwardness must not be sought in the efforts of its individual countries but in the collective effort of integrated economies of the various countries. These two reasons are fundamental to explaining the ineffectiveness of four decades of the inflow of development aid. Our methodology is to identify three main areas traditionally acknowledged as the major obstacles to Africa’s economic, social, and political development, - economics, politics and security - and then proceed to demonstrate that these are hindrances that can be removed only by sub-regional economic and political amalgamation.